2019
DOI: 10.1088/1755-1315/385/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Terrestrial Laser Scanner Measurement in Slope Monitoring

Abstract: Dense 3D point clouds provided by terrestrial laser scanner (TLS) has demonstrated significant reliability of TLS in landslide monitoring. However, existence of errors in measurement is inevitable which eventually has decreased the quality of TLS data. To concretely measure the capability of TLS in landslide monitoring, this study has performed two epoch measurements using tacheometry (for benchmarking) and TLS (Topcon GLS-2000) at Kulim Techno City, Kedah, Malaysia. Sixteen (16) artificial targets were well-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, this method also has some disadvantages, including a high volume of generated point clouds, especially for large areas, and the problem of accurately registering these point clouds. Based on this, there is some research about the reliability and accuracy of using TLS for monitoring [49,50]. In recent years, TLS and UAV photogrammetry have been used together to cover the disadvantages of using one of the methods alone [51][52][53][54][55].…”
Section: Terrestrial Laser Scannersmentioning
confidence: 99%
“…However, this method also has some disadvantages, including a high volume of generated point clouds, especially for large areas, and the problem of accurately registering these point clouds. Based on this, there is some research about the reliability and accuracy of using TLS for monitoring [49,50]. In recent years, TLS and UAV photogrammetry have been used together to cover the disadvantages of using one of the methods alone [51][52][53][54][55].…”
Section: Terrestrial Laser Scannersmentioning
confidence: 99%
“…The impact of the incidence angle on the point cloud data was tested, and it was found that about 80% of the data would be lost when the laser incidence angle was greater than 70 degrees [ 84 ]. The presence of high incidence angles in TLS measurements has limited the capability to identify the significant displacement of the targets [ 85 ]. Systematic and random errors affect the coordinates of each point in the point cloud, which is directly related to the data quality and subsequent processing of the point cloud.…”
Section: Key Issues In the Application Of Tls Technologymentioning
confidence: 99%